Unpacking the Financial Incentives in Health by Revisiting India’s “Safe Motherhood Program” - Baulia Susmita (Germany, 2025)
This paper investigates India’s nationwide health reform to understand its various channels of effect. The reform entitled socio-economically backward mothers with cash transfer if they chose to give birth at public health institutions, and simultaneously employed ASHAs as a direct link between pregnant women and the public healthcare delivery system. Using variations in mothers’ eligibility and differential implementation of ASHAs across states, birth-related outcomes are evaluated in a difference-in-difference framework. Results show that eligible mothers with both cash transfer and ASHA’s guidance outperformed those receiving only cash transfer, in institutional birth rate and timely initiation of breastfeeding. An improved outcome in the ASHA’s presence alongside the conditional cash transfer argues for the vitality of the former’s role in spreading information on the importance of health and the uptake of public healthcare.